Identification of Factors Affecting the Selection of Women's Gyms - Abbas Naghizadeh-Baghi; Masoud Imanzadeh; Mitra Lalfam; Farzad Nobakht Sareban; Majid Javid (Research in Sport Management and Marketing)
Purpose: Gymnasiums need to identify and strengthen the factors influencing customer attraction to grow and survive. Examining and recognizing the factors that lead to attracting people to such places is important in sports management. The purpose of this study was to identify and classify the factors affecting the selection of women's gymnasium using factor analysis method.Methods: The research method is applied and the main strategy of the research is a mixed-method and it was implemented in the field. The statistical population of the study includes all customers of       Ardabil women's gyms. Using the Cochran's formula, the sample size was 384 people and the random sampling method was used to select the sample units. The measuring tools included interviews and questionnaires. Participants were selected using purposeful sampling for the interview and theoretical saturation was reached when the number of participants reached 12. Open coding was performed using MAXQDA12 software and a research questionnaire was developed using 44 codes. The data were analyzed by SPSS26 software using Exploratory Factor Analysis test.Results: The results showed that 44 final characteristics affecting the selection of the gym were factorized into 8 factors by factor analysis and these factors explain 67% of the total variance.Conclusion:   Factors influencing the selection of women's gymnasiums in order of priority include Physical Evidence, process, Place, price, product, People, Promotion and Privacy.